Family And Social Support on Successful Treatment of Pulmonary Tuberculosis Patients: A Cross-Sectional Study - Rahmadhani, Velia; Setiyadi, Agung; Wardani, Nuniek Setyo; Pamungkas, Indra Gilang (Celebes Nursing Journal, 2024)
Introduction: Eradicating Tuberculosis is one of the government's three main priorities in the health sector, so the success of pulmonary TB treatment really needs to be considered. The family and social environment are the closest things for patients to be able to comply and be successful in carrying out treatment. Objectives: This research aims to assess the relationship between family and social support to successful treatment of pulmonary TB patients. Methods: This study used a cross-sectional design with 72 respondents who had completed TB treatment for 6 months. Results: The results of the study showed that there was a significant relationship between family and social support on the success of pulmonary TB treatment with p-value was 0.005 (p-value < 0.05) and 0.001 (p-value < 0.05). Conclusion: Family and social support have a meaningful relationship. The family and social environment of patients with pulmonary TB must provide support and motivation for the patient to be able to complete the treatment he is receiving.